The school is Also a Place for “La Ursa”! - Santa Cruz, Jevison (Revista do Colóquio, 2025)
This paper presents how a fourth-grade class from a municipal school in Abreu e Lima, Pernambuco, experienced the local carnival through the traditional folk game La Ursa. The research followed a qualitative methodology with descriptive and bibliographic approaches, along with systematic and participant observation. Art classes were guided by the Triangular Approach, developed by Ana Mae Barbosa. As outcomes, the experience fostered empathy, teamwork, conflict resolution, and the notion of democratic participation, exemplified by the collective choice of the theme.
Keywords: popular culture; art education; la ursa